2022
DOI: 10.1111/cod.14086
|View full text |Cite
|
Sign up to set email alerts
|

Perioral photoallergic dermatitis to promazine hydrochloride

Abstract: Perioral photoallergic dermatitis to promazine hydrochloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There is extensive literature that explores the chemical and biological basis of druginduced photosensitivity [72,[74][75][76][77][78] but not much in the case of cosmetics. In this context, a recent examination by Hofmann et al [69] identified a total of 393 distinct drugs or drug compounds reported as photosensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature that explores the chemical and biological basis of druginduced photosensitivity [72,[74][75][76][77][78] but not much in the case of cosmetics. In this context, a recent examination by Hofmann et al [69] identified a total of 393 distinct drugs or drug compounds reported as photosensitizers.…”
Section: Discussionmentioning
confidence: 99%